Avaliação de algumas qualidades das tuberculinas de uso animal no Brasil - José Maria Wiest (1972)
Qualities of four tuberculin samples, for animal use, produced and/or employed in Brazil, are estudied trough microbiological tests, experimental inoculations, biochemical and biological titration. They are analysed on aspects of origin, presentation, type and destination, presence of preservatives and stabilizants, specific and secondary sterility. toxicity, biochemical and biological titers and loss of potency. Problems were observed in the biochemical and biological standardization aspects, as well as marked loss of potency in sample. The uniformization necessity of the product, in international standard values, is recognized for better viability of epidemiological studies and efficiency of control measures of turberculosis, in our country.